The impact of fiscal policy announcements by the Italian government on the sovereign spread: a comparative analysis - Matteo Falagiarda; Wildmer Daniel Gregori (European Central Bank (ECB), 2015)
This paper attempts to evaluate the impact of fiscal policy announcements by the Italian government on the long-term sovereign bond spread of Italy relative to Germany. After collecting data on relevant fiscal policy announcements, we perform an econometric comparative analysis between the three administrations that followed one another during the period 2009-2013. The results indicate that only fiscal policy announcements made by members of Monti's cabinet had a significant impact on the Italian spread. We argue that these findings may be partly explained by a credibility gap between Monti's technocratic administration and Berlusconi's and Letta's governments.
Keywords: E43; E62; G01; G12; 330; fiscal policy announcements; GARCH models; interest rate spread; political communication; sovereign debt crisis